User keyword preference: the Nwords and Rwords experiments. (27th October 2008) - Pfitzner, Darius; Treharne, Kenneth; Powers, David
Everyday, millions of people use some form of text-based interface to search inefficiently for information. This reflects a lack of penetration of key developments in Human Computer Interaction (HCI) designed to expedite document retrieval. In the context of document search, the value of textual language is self-evident for searching natural language documents. However, there has been little human factors research into general user preferences such as the number of words preferred to describe or search for a document. Such heuristics can help to balance processing overheads of tasks like clustering against user cognitive load in the realisation of, overall, more efficient document retrieval process. We report the results from two internet delivered experiments designed to obtain this heuristic information.